ARAHAN KEBIJAKAN PENGGUNAAN LAHAN PERMUKIMAN BERBASIS BENCANA TSUNAMI DI KABUPATEN PESISIR SELATAN - Veni Veni (Geography Education Study Program, Faculty of Teacher Training and Education, 2019)
This research begins from phenomena of the tsunami disaster that could potentially occur in Kabupaten Pesisir Selatan. This study aimed to analyze the suitability of land for settlements in the zone are not at risk of tsunami and settlement development policy directives based tsunami. This research classified as descriptive and used a survey method. The mapping unit used is a unit of landforms. units in research area was varied so that sample technique used here was stratified random sampling. The research showing that residential suitability in Kabupaten Pesisir Selatan divide into two areas, its : suitable area for settlement (4007,225 km) and unsuitable area for settlement (1742,665 km). The suitable area based on tsunami there are four areas, its (i) Settlements with moderate risk of tsunami (946,036 km), (ii) Settlements with low risk tsunami (3061,189 km), (iii) Unsuitability settlements with moderate risk tsunami (838,710 km), (iv)Unsuitability settlements with low risk tsunami (903,954 km). Policy directives use for settlements based on tsunami disaster with priority by four alternative policy its : a. tsunami disaster mitigation through the construction of shelters and evacuation route, b. Knowing risk zone tsunami for early warning system, c. relocation of settlements gradually to people who live in areas at risk of tsunami, d. preparing land designated for residential area-based tsunami.